A comparison of older drivers' driving patterns during a naturalistic on-road driving task with patterns from their preceding four-months of real-world driving. (May 2020) - Koppel, S.; Liu, P.Y.; Griffiths, D.; Hua, P.; St. Louis, R.M.; Stephan, K.; Logan, D.B.; Di Stefano, M.; Darzins, P.; Porter, M.M.; Mazer, B.; Gélinas, I.; et al.
Highlights: 208 older drivers completed a naturalistic on-road driving task (eDOS) Compared driving patterns during the eDOS and real-world driving (RWD) trips. Sub-trips of home-to-first-destination during the eDOS resembled RWD trips that started from home. Potential to use eDOS to assess at-risk older drivers for modified (local area) licences. Abstract: This study compared older drivers' driving patterns during a naturalistic on-road driving task (i.e., eDOS driving task) with their real-world driving from the preceding four-month period. Two hundred and eight participants (Male: 68.8%; Mean age = 81.5 years, SD = 3.3 years) completed the eDOS driving task in their own vehicle which commenced from their home and followed a self-selected route. Participants' driving patterns were collected via an in-car recording device that was installed in their vehicle. This study examined the sub-trip from participants' homes to their first destination during the eDOS driving task. The median sub-trip distance was 4.4 km (Q1 = 2.8, Q3 = 6.4). Across the four-month period of real-world driving, participants completed a median of 151 driving trips from their home (Q1 = 103.0, Q3 = 202.7), with a median trip distance of 2.7 km (Q1 = 1.1, Q3 = 5.8). Most participants' eDOS driving task trip distance was classified as representative of their real-world driving trip distances (95.2%). By mapping GPS coordinates for driving pattern data with road types and roadways, most eDOS driving task trips included roadways that were actively used during their real-world driving (85.0%). During the preceding four-month period of real-world driving, most participants had visited the first nominated destination during the eDOS driving task at least once per month (77.4%). Given the increasing international interest and use of modified (local area) licences, these findings suggest that naturalistic on-road driving tasks could be used by licensing authorities to assess potentially at-risk older drivers within their own driving environments.